Endometrial preparation using gonadotropin-releasing hormone agonist prior to frozen-thawed embryo transfer in women with repeated implantation failure: An RCT - Robab Davar; Saeideh Dashti; Marjan Omidi (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Preparation of endometrial thickness in frozen-thawed embryo transfer (FET) is extremely important, particularly in repeated implantation failure (RIF) patients. Objective: This study aimed to investigate the clinical outcomes of FET cycles among RIF women, based on the effects of administering gonadotropin-releasing hormone (GnRH) agonist prior to estrogen-progesterone preparation of the endometrium. Materials and Methods: In this randomized clinical trial, 67 infertile women who were candidates for FET were divided into two groups: A) case group (n = 34), treated with GnRH agonist prior to endometrial preparation and B) control group (n = 33), which received the routine protocol. (6 mg daily estradiol started from second day) The clinical outcomes) including chemical and clinical pregnancy, in addition to implantation rates, were compared between the two groups. Results: The results showed no significant differences in women's age (p = 0.558), duration (p = 0.540), type (p = 0.562), and cause of infertility (p = 0.699). Regarding pregnancy and implantation rates, there was a trend toward an increase in the case group; however, differences were not statistically significant. Conclusion: Although our results showed no significant differences between groups. Because there are trends to better results in case group larger sample size may show significant difference.